Opportunities and Obstacles Associated With Sequential Immune Reconstitution Therapy for Multiple Sclerosis: A Case Report - Garbo, Riccardo; Cutuli, Daniela; Lorenzut, Simone; Gigli, Gian Luigi; Bagatto, Daniele; Valente, Mariarosaria (Frontiers in Neurology, 2021)
Cladribine is an effective disease-modifying treatment for relapsing-remitting multiple sclerosis that acts as an immune reconstitution therapy and is administered in a pulsed manner. Despite its efficacy, severe disease reactivation early after treatment represents a serious clinical problem, and clear evidence to guide the management of such a situation is lacking. Here, we describe the case of a patient experiencing considerable disease activity during the 1st year after the initiation of cladribine treatment. The patient was switched to alemtuzumab and, therefore, received double immune reconstitution therapy. Data regarding this approach are lacking, and real-world observations may be of interest. Despite achieving good control of disease activity, we observed several serious infectious complications. Our results suggest that sequential immune reconstitution therapies may be effective; however, at the price of higher susceptibility to infections.